2013
DOI: 10.1080/09640568.2012.698984
|View full text |Cite
|
Sign up to set email alerts
|

Re-thinking sustainability indicators: local perspectives of urban sustainability

Abstract: The measurement of sustainability is not only a contentious issue, but one which has captured the attention of both academics and politicians since the late 1980s. A plethora of methods and approaches have been developed over the last decades or so, from rapid measurements as inputs to specific projects, to longer-term processes of research, monitoring and wider learning. But perhaps, the most influential ones have been indicators. The tensions between expert-led and citizen-led models of indicator development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
232
0
21

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(256 citation statements)
references
References 61 publications
3
232
0
21
Order By: Relevance
“…This study demonstrated the complex interactions that existed between environmental and socio-economic factors on land-use change, reinforcing the reasons identified by Verburg et al (2004), Claessens et al (2009), andLi, Zhou, andOuyang (2013), leading us to rethink sustainability of local urban settlements (Turcu 2014). For future sustainable development and prevention of hazardous events it is important to take the following into account (1) the design and implementation of a Master Plan must consider the physical parameters of the landscape, which are essential in producing thematic mapping and support land-use restrictions and constraints, (2) given the role of actors in the transformation processes, measures should be implemented that effectively involve different actors and levels of expertise in the planning process.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated the complex interactions that existed between environmental and socio-economic factors on land-use change, reinforcing the reasons identified by Verburg et al (2004), Claessens et al (2009), andLi, Zhou, andOuyang (2013), leading us to rethink sustainability of local urban settlements (Turcu 2014). For future sustainable development and prevention of hazardous events it is important to take the following into account (1) the design and implementation of a Master Plan must consider the physical parameters of the landscape, which are essential in producing thematic mapping and support land-use restrictions and constraints, (2) given the role of actors in the transformation processes, measures should be implemented that effectively involve different actors and levels of expertise in the planning process.…”
Section: Discussionmentioning
confidence: 99%
“…Para o alcance do objetivo desta pesquisa, operacionalizaram-se as duas primeiras etapas do ProKnow-C, ou seja, (i) a formação de um portfólio de artigos relevantes e alinhados ao tema, e (ii) a análise bibliométrica das variáveis básicas (artigos, periódicos, autores e ferramentas de AD) e variáveis avançadas (nível do sistema/ferramenta de avaliação e ciclo de vida do sistema/ferramenta), que respondem pelo mapeamento da literatura e possibilitam a geração de conhecimento sobre o tema. (BERARDI, 2013;TURCU, 2013;KOMEILY;SRINIVASAN, 2015;AHVENNIEMI et al, 2016), qualidade de vida (ALQAHTANYA et al, 2012) e cultura (AMEEN et al, 2015).…”
Section: Referencial Teórico: Avaliação De Desempenho No Desenvolvimeunclassified
“…With the development of these indicators, people will easily manage their own behaviour with reference to their individual goals and they will be motivated continue improvements through new policy intervention and incentives. Turcu [11] states that what seems obvious and important to experts at the 'top' of indicator development might seem less important to citizens at its 'bottom'. By including citizens' values and priorities to indicator development, the focus of indicators could shift from 'input' and 'process' to 'outcome' oriented understanding of local sustainability which provides policy-makers with relevant information to assess sustainability.…”
Section: Review Of the Sustainable Development Indicator Initiativesmentioning
confidence: 99%